PENDAMPINGAN KADER POSYANDU REMAJA SEBAGAI UPAYA PENCEGAHAN STUNTING DI KELURAHAN KRANJI KABUPATEN BANYUMAS (Universitas Wijayakusuma Purwokerto, 2023)
Stunting cases in Indonesia are still a serious health problem that cannot be completely resolved. Several previous studies stated that tackling stunting cases can mainly be done through efforts to change behavior and empower the community. This service activity is aimed at empowering youth posyandu cadres in the Kranji Village in dealing with and preventing stunting cases. This activity was carried out in February-June 2023 in Kranji Village, Banyumas Regency. The main target of this activity is youth posyandu cadres in the Kranji Village. This empowerment activity is carried out attractively through a socialization mechanism during youth Posyandu activities. Indicators of success are seen through the presence of young posyandu cadres, increased knowledge and skills of youth posyandu cadres. The results of the empowerment activities stated that there was an increase in understanding of the efforts that could be taken to prevent stunting in the youth Posyandu cadres, Kranji Village, Purwokerto.